2020
DOI: 10.1242/dmm.045021
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2/HO-1 mediates neuroprotective effects of pramipexole by attenuating oxidative damage and mitochondrial perturbation after traumatic brain injury

Abstract: Pramipexole (PPX), a D2-like receptor agonist, is generally used in the treatment of Parkinson's disease and restless leg syndrome. Its neuroprotective effects have been shown against various neurological disorders. Recent research work has demonstrated that PPX exerts neuroprotection through mitochondria. However, the neuromodulator-related effects of PPX against traumatic brain injury (TBI) remain unexplored. The present study, therefore, investigated the mechanism of neuroprotection by PPX against oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
(70 reference statements)
1
11
0
1
Order By: Relevance
“…The results are similar to other studies that proved stimulation of the NRF2 pathway via oxidative stress after TBI [92]. Not only NRF2 but the expression of the HOMX1 gene is also upregulated in this study as observed by Salman et al [93]. Saffron treatment enhanced the upregulation of NRF2, and HMOX1 to control the generated oxidative stress.…”
Section: Plos Onesupporting
confidence: 92%
“…The results are similar to other studies that proved stimulation of the NRF2 pathway via oxidative stress after TBI [92]. Not only NRF2 but the expression of the HOMX1 gene is also upregulated in this study as observed by Salman et al [93]. Saffron treatment enhanced the upregulation of NRF2, and HMOX1 to control the generated oxidative stress.…”
Section: Plos Onesupporting
confidence: 92%
“…There have been some drugs or methods used to alleviate TBI-related neurological disorders by targeting Nrf2 and HO-1. For example, the D2-like receptor agonist pramipexole activates the Nrf2/HO-1 signaling pathway to serve a neuroprotective effect following TBI ( 9 ). The behavioral changes and reduction of oxidative stress in Wistar rats treated with tannin following TBI were attributed to the activation of PGC-1α/Nrf-2/HO-1 signaling pathway ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined antioxidant therapy to inhibit NOX 2 and activate Nrf2 decreases secondary brain damage and improves functional recovery following TBI ( 8 ). The use of pramipexole (D2-like receptor agonist) to activate the transcription process of Nrf2 and its downstream detoxification enzyme heme oxygenase-1 (HO-1) has a significant neuroprotective effect following TBI ( 9 ). Therefore, it is important to determine if compounds with antioxidant properties, such as wogonin, a flavonoid compound extracted from the plant Scutellaria baicalensis Georgi and used in traditional Chinese medicine, are effective treatments for reducing secondary TBI injury.…”
Section: Introductionmentioning
confidence: 99%
“…Считается, что потеря митохондриальной функции из-за ишемии в виде окислительного стресса и активации факторов апоптоза играет решаю щую роль в развитии вторичного повреждения и последующей гибели нейронов головного мозга. Неоднократно обсуждалось, что АДР D 2 / D 3 -рецепторов способствуют нейропротекции при БП именно за счет механизмов стабилизации работы митохондрий, уменьшения количества свободных радикалов и регуляции апоптоза [36]. Применение данных препаратов в острый период повреждения клеток мозга при инфаркте может влиять как на формирование очага повреждения, так и на клинический исход инсульта.…”
Section: нейропротекция при использовании агонистов дофаминовых рецеп...unclassified